A simple isothermal nucleic acid amplification method for the effective on-site identification for adulteration of pork source in mutton. (April 2019) - Liu, Rui; Wang, Xiudan; Wang, Xuejiao; Shi, Yanjing; Shi, Chao; Wang, Wei; Ma, Cuiping
Abstract: As meat adulteration issue is becoming increasingly prominent worldwide, it is crucial to realize on-site detection with simple equipment. Conventional nucleic acid amplification methods are reliable but the requirement of complex equipment, skilled technicians and long operation time limit their on-site use. Here, a simple denaturation bubble-mediated strand exchange amplification method (SEA) requiring only a pair of primers and one polymerase was first reported for identifying adulteration of pork source by targeting the specie-specific mitochondrial DNA sequence. The SEA method displayed good specificity for pork and could detect as low as 30 pg/μL pork DNA. In binary mixtures, the SEA method could detect 1% pork meat total DNA by both colorimetric and fluorescence determination, fulfilling the requirement of artificial meat adulteration. Excitedly, the whole detection process could be finished within 1 h by coupling with fast tissue DNA extraction method, only requiring a simple heating block. Therefore, with simplicity and rapidity, SEA method will be suitable for on-site meat species identification.